Neurogenetic evidence in the courtroom: a randomised controlled trial with German judges - Fuß, Johannes; Dreßing, Harald; Briken, Peer (Journal of medical genetics, 2015)
Background Prominent court decisions and recent research suggest that introduction of neurogenetic evidence, for example, monoamine oxidase A alleles, may reduce the sentence of convicted psychopaths. Here, we are aiming to demonstrate that judges’ response to neurogenetic evidence is highly influenced by the legal system in which they operate. Methods Participating German judges (n=372) received a hypothetical case vignette of aggravated battery, and were randomly assigned to expert testimonies that either involved a neurogenetic explanation of the offender's psychopathy or only a psychiatric diagnosis of psychopathy. Testimonies were presented either by the prosecution or defence. Results Neurogenetic evidence significantly reduced judges’ estimation of legal responsibility of the convict. Nevertheless, the average prison sentence was not affected in the German legal system. Most interestingly, analysis of judges’ reasoning revealed that neurogenetic arguments presented by the prosecution significantly increased the number of judges (23% compared with ∼6%) ordering an involuntary commitment in a forensic psychiatric hospital. Such an involuntary commitment due to diminished or absent legal responsibility may last much longer than a prison sentence in the German legal system. Conclusions Our data, thus, demonstrate the socially contingent nature of legal responses to neurogenetic evidence in criminal cases.